THE EFFECT OF SHORT DIALOGUE MEMORIZATION ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS AT SMP IT AL IHSAN BOARDING SCHOOL - Bella Windiana Putri; Syofia Delfi; Jismulatif ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to investigate the effect of using Short Dialogue Memorization on the speaking ability of the second year students at SMP IT Al Ihsan Boarding School, Sik Hulu, Kampar. This study was pre-experimental research. The population of this research was the students in Hunain class at SMP IT Al Ihsan Boarding School. This research was conducted by applying Short Dialogue Memorization in teaching speaking to the pre-experimental group (Hunain Class) selected by employing cluster random sampling method. There were 20 students in pre-experimental group, who had a pre-test, then they were taught by using Short Dialogue Memorization, then they finally had a post-test to see the increase of their scores. After all data were collected, the researcher calculated them by using t-Test. This study formed findng with the correlation was 0.931, it can be concluded that there was a significant effect of using Short Dialogue Memorization on the speaking ability of the second year students at SMP IT Al Ihsan Boarding School that could be seen from the improvement of students’ scores in post-test.Keywords: Speaking, Speaking Ability, Short Dialogue Memorization